Courtesan, Hetaira: Sade’s heroine philosopher (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This article aims at examining the fictional characterization of women philosophers during the eighteenth century, focusing on Donatien Alphonse François de Sade’s novel, Histoire de Juliette, ou les prospérités du vice. We seek to show that the marquis’s heroines philosophers (personified by libertine women) in Histoire de Juliette are modeled after the figure of the hetaira in Classical Greece. We analyze two sets of references to the hetairai that appear in the aforementioned novel: the description of Clairwil, one of Juliette’s libertine tutors and partners, and the participation of Aspasie, Phryné and Lais in Juliette’s libertine entourage.
Keywords: Sade; Hetaira; histoire de Juliette; women philosophers.